Molecular insights of the class A scavenger receptor, macrophage receptor with collagenous structure (MARCO) in Nibea albiflora - Yibo Sun; Weimin Liao; Yue Liu; Libing Zheng; Dongdong Xu; Changfeng Chi; Zhenming Lv; Huihui Liu (Aquaculture Reports, 2021)
The macrophage receptor with collagenous structure (MARCO) plays a key role in bacteria-binding innate immune response. According to the transcriptome data MARCO was identified from the spleen (designated as NaMARCO) of Nibea albiflora, its full-length (GenBank accession no. MN243703.1) was 1788 bp, and the open reading frames (ORF) was 1278 bp encoding a polypeptide of 425 amino acids with predicted pI/MW 8.72/43.61 kDa, which had the conserved scavenger receptor cysteine-rich (SRCR) domain similar to its mammalian counterparts. The BLASTp analysis and phylogenetic relationship strongly suggested that NaMARCO shared high similarity with known MARCO, especially at theSRCR domain. The expression of NaMARCO was detected in six tissues (liver, spleen, head kidney, muscle, gill and stomach) and the highest expression appeared in the spleen. After being challenged with Pseudomonas plecoglossicida and poly I:C, NaMARCO expressed with a time-dependent manner in the spleen, and significantly got the peak at 48 h (9.86 times compared with 0 h) for P.plecoglossicida infection, but the peak appeared at 2 h by being challenged with poly I:C (5.18 times compared with 0 h). The results suggested that NaMARCO might be involved in the immune defence of N.albiflora. In addition, subcellular localization of NaMARCO was performed in EPC cells (epithelial cells from fathead minnow), and it was expressed mainly on the cell membrane, the endoplasmic reticulum and the organelle membrane surrounding the nucleus appeared positive signals. These results suggested that NaMARCO, as an important kind of transmembrane scavenger receptors, had a potential role in the immune defense system of N.albiflora against the pathogen.